Prioritizing the product design specification of side-door impact beam using analytic hierarchy process method - Shaharuzaman, Mohd Adrinata; Salit, Mohd Sapuan; Mansor, Muhd Ridzuan; Mohamed Yusoff, Mohd Zuhri (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2018)
Product design specification (PDS) is one of the elements in the product development process. To develop the side-door impact beam, six criteria of the PDS have been chosen and compared by ten decision makers using pairwise comparison with nine-point scale judgement by Analytic Hierarchy Process (AHP) method. Each criterion by each decision makers were sum up and the average data calculated. The average data is the result of the priority vector and it shows that the AHP can prioritize the PDS of side-door impact beam from highest to lowest which are performance, product cost, weight, environment, disposal and size.